The Taste of Art : Cooking, Food, and Counterculture in Contemporary Practices - D'Ayala Valva, Margherita; Bottinelli, Silvia (Book collections on Project MUSE., 2017)
This book offers a sample of scholarly essays that examine the role of food in Western contemporary art practices. The contributors are scholars from a range of disciplines, including art history, philosophy, film studies, and history. As a whole, the volume illustrates how artists engage with food as matter and process in order to explore alternative aesthetic strategies and indicate countercultural shifts in society. The collection opens by exploring the theoretical intersections of art and food, food art's historical root in Futurism, and the ways in which food carries gendered meaning in popular film. Subsequent sections analyze the ways in which artists challenge mainstream ideas through food in a variety of scenarios. Beginning from a focus on the body and subjectivity, the authors zoom out to look at the domestic sphere, and finally the public sphere. -- Provided by the publisher.